Phallic symbols, fertility and enjoyment of life in Rome: new approaches from the material culture of Pompeii - Garraffoni, Renata Senna; Sanfelice, Pérola de Paula (Romanitas - Revista de Estudos Grecolatinos, 2017)
The aim of this paper is to focus on gender studies and their contributions to new approaches to Classical Archaeology regarding the Early Principate. First, we shall focus on theory and its specificity in Brazil and second we will study a series of lamps and apothropaic objects from Pompeii to propose a new approach to this type of material culture. We shall argue that is urgent to move beyond phallocentric or pornographic views from the Roman past.
Keywords: Pompeii; Phallic material culture; Gender studies